PENGARUH MOTIVASI DAN KEPUASAN TERHADAP KINERJA PETERNAK AYAM BROILER POLA KEMITRAAN (Contract Farming) DI KOTA PEKANBARU - Efrina Rizkiyah Pohan; Cepriadi Cepriadi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2020)
This research aims to (1) know the level of motivation of broiler breeders partnership (contract farming) in Pekanbaru City, (2) know the level of satisfaction of broiler breeders partnership (contract farming) in Pekanbaru City, (3) know the level of performance broiler breeders partnership (contract farming) in Pekanbaru City and (4) analyze the influence of motivation and satisfaction on the performance of broiler breeders partnership (contract farming) in Pekanbaru City. This research uses secondary data and primary data, secondary data obtained from the central statistical agency, primary data obtained by direct interview using the questionnaire. Retrieval method using convenience sampling technique. Qualitative data analysis is Likert-scale interpretation and multiple linear regression interpretation with SPSS 23 include: coefficient of determination, F test, and t test. Likert scale results in the motivation variable showed a score of 3.69, this shows that breeders feel motivated in partnering. The value of satisfaction score is 3.71 which means in partnership of breeders included in the category of satisfaction. As for the performance variables obtained average score is 3.15 indicates that the breeder is in the category well enough in doing business. Multiple linear regression results show that the coefficient of determination is 0.623, meaning that 62.3 percent of performance is influenced by motivation and satisfaction variables, while the remaining 37.7 percent is influenced by other variables outside the equation model.